A framework for the development of a National Crypto-Currency - Abdullah, Adam; Mohd Nor, Rizal (Canadian Center of Science and Education, 2018)
This paper seeks to provide a conceptual framework as to whether a central bank or a monetary authority should issue a crypto-currency given available technology and what are the consequences of doing so. Under the fiat standard the value and purchasing power of money has experienced an exponential decay, whilst prices have increased exponentially. Typically, a central bank is responsible for monetary and financial stability, including settlement and payment mechanisms. A proposed methodology is provided that involves both quantitative and qualitative analysis to measure the comparative monetary performance, stress testing and impact assessment of a new crypto-currency that includes backing by gold, silver and a basket of commodities. The scope of the proposed framework involves a monetary economic analysis, supported by a technological investigation, under the framework of Shari’ah compliance, to explore an impact assessment of the adoption of a national crypto-currency. The significance of this study is that, it provides a framework for the development of a new national crypto-currency, which retains its’ store of value in terms of monetary performance and price stability, that would also investigate whether it’s implementation is viable.